Sentiment Analysis of the Public on the Deployment of Smart Robots in Indonesia Using the Naïve Bayes Method - Muthmainnah, Muthmainnah; Rudiman, Rudiman; Yulianto, Fendy (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2025)
In this digital era, social media platforms have become the primary means for the public to express opinions on current issues, including discussions about the roles of robots and artificial intelligence in replacing human jobs. The focus of this community service is to investigate public sentiment regarding the implementation of smart robots in Indonesia, utilizing text-based sentiment analysis. The Naïve Bayes method is chosen as the approach to classify sentiments, overcoming challenges such as language and cultural variations. Through data testing and training, this research successfully achieved an accuracy rate of 98%, with high Precision, Recall, and F1 Score. The results provide valuable insights for companies and organizations that need to understand public perspectives on technological advancements and their impact on human employment.